2021
DOI: 10.29145/jmr/82/08
|View full text |Cite
|
Sign up to set email alerts
|

SMEs, Economic Growth, and Business Incubation Conundrum in South Africa. A Literature Appraisal

Abstract: Despite the South African government's desire to encourage economic growth via SME growth, attempts to ameliorate the difficulties encountered by SMEs are often hindered by a lack of resources, one of which is business incubation. This paper employs a descriptive literature review to declutter the varying concerns of SME growth and development from the narratives around the role of business incubators (BIs) and the government. This, we believe, would provide clarity on the challenges faced by SMEs deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Similarly, financial planning capabilities have no impact on the semi-formal financial accessibility of incubated entrepreneurs as well. It is also an unexpected result as it contradicts most studies, including the study by Robison et al (2021), which has shown that financial planning capabilities significantly impact financial accessibility. This could be because semi-formal financiers need to use financial planning variable items like preparing quarterly, semi-annual and annual budgets.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Similarly, financial planning capabilities have no impact on the semi-formal financial accessibility of incubated entrepreneurs as well. It is also an unexpected result as it contradicts most studies, including the study by Robison et al (2021), which has shown that financial planning capabilities significantly impact financial accessibility. This could be because semi-formal financiers need to use financial planning variable items like preparing quarterly, semi-annual and annual budgets.…”
Section: Discussionmentioning
confidence: 67%
“…Limited accessibility to semi-formal finance among small and medium-incubated entrepreneurs is associated with their lack of financial management capabilities (Yi et.al., 2022). In turn, financial management capabilities influence financial accessibility (Robison et al, 2021). Incubated entrepreneurs with strong financial management skills are viewed as more creditworthy by semi-formal lenders (FinScope, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial incubation in South Africa has been growing in significance over the past decade as the country recognises the importance of fostering innovation, job creation, and economic growth through startups and small businesses (Lose & Tengeh, 2015;Van der Spuy, 2019). South Africa has adopted business incubation as a tool to strengthen the economy through SMEs (Dubihlela & van Schalkwyk 2014;Rens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%